2020
DOI: 10.1002/joc.6525
|View full text |Cite
|
Sign up to set email alerts
|

The Pacific decadal oscillation modulates the relation of ENSO with the rainfall variability in coast of Ecuador

Abstract: Worldwide and likewise in Ecuador, the 1982–1983 and 1997–1998 El Niño Southern Oscillation (ENSO) events had devastating effects in the economic and human dimension. Thus, scientists and decision markers look for a deeper knowledge about ENSO and its phases El Niño (EN)/La Niña (LN). Recent research highlights the changing nature of ENSO under opposite conditions of the Pacific Decadal Oscillation (PDO), making the assessment of the ENSO–PDO relation in Ecuador urgent. This study explores the time‐frequency c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The AMO affects hydroclimate in this region through alterations of the SALLJ, with active SALLJ days during negative AMO phases in association with negative precipitation anomalies over the Andes-Amazon transition region and the Atlantic ITCZ (Jones and Carvalho, 2018). More recently, Campozano et al (2020) highlight that PDO modulates the ENSO influence on precipitation in the eastern Ecuadorian Andes, where the PDO warm phase enhances (reduces) precipitation when in phase with El Niño (La Niña). Furthermore, the PDO warm phase influences the connection between ENSO Canonical events and precipitation in the eastern Ecuadorian Andes while this link is not affected for the ENSO Modoki events (Campozano et al, 2020).…”
Section: Decadal Variabilitymentioning
confidence: 96%
“…The AMO affects hydroclimate in this region through alterations of the SALLJ, with active SALLJ days during negative AMO phases in association with negative precipitation anomalies over the Andes-Amazon transition region and the Atlantic ITCZ (Jones and Carvalho, 2018). More recently, Campozano et al (2020) highlight that PDO modulates the ENSO influence on precipitation in the eastern Ecuadorian Andes, where the PDO warm phase enhances (reduces) precipitation when in phase with El Niño (La Niña). Furthermore, the PDO warm phase influences the connection between ENSO Canonical events and precipitation in the eastern Ecuadorian Andes while this link is not affected for the ENSO Modoki events (Campozano et al, 2020).…”
Section: Decadal Variabilitymentioning
confidence: 96%
“…However, a strong influence of the oceanic indices was found (Table 5), and actually it is the highest accumulated importance of the oceanic indices among the 10 clusters. The influence that Tropical Pacific SST anomalies (mainly related to ENSO) have on precipitation in this area is well-known (Rossel and Cadier, 2009;Bendix et al, 2011;Sulca et al, 2018;Tobar and Wyseure, 2018;Zambrano Mera et al, 2018;Campozano et al, 2020) and has been confirmed by novel approaches such as the one in Landshuter et al (2020) in this region. In fact, among the oceanic indices shown in Table 4 for cluster 5, only one (TSA) is not related to ENSO.…”
Section: Identification Of Leading Precipitation Drivers For Each Clu...mentioning
confidence: 71%
“…However, one significant limitation is that these types of data are available only since 1979. These relatively short‐term measurements hinder the appropriate characterization and identification of decadal and interdecadal climatic processes (Hartigan et al ., 2020), such as the PDO and the AMO that have been found to play a role in precipitation in the region (Arias et al ., 2015b; Campozano et al ., 2020). To overcome this obstacle, alternative datasets with longer time series should be considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PDO covers the Northern and Equatorial Pacific, while the IPO has a tripole pattern also covering the Southern Pacific, however, both oscillations are directly correlated (Henley, 2017). Several studies indicate that teleconnections between El Niño and precipitation in South America are strengthened during the warm phase of the IPO (PDO) (Andreoli and Kayano, 2005;Wang and Liu, 2016;Campozano et al, 2020;Nguyen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%